Sudden development of adult-onset type II citrullinemia after total gastrectomy: a case report - Ryuji Komine; Keisuke Minamimura; Akihiro Watanabe; Atushi Shimizu; Kazuhiko Mori; Toru Hirata; Takashi Kobayashi; Sotaro Akatsuka (Surgical Case Reports)
Abstract Background Adult-onset type II citurullinemia is an autosomal recessive disorder characterized by recurrent encephalopathy with hyperammonemia resulting from high plasma citrulline and ammonium levels. This report describes a rare case of adult-onset type II citurullinemia that occurred in a patient who only had the heterozygote mutation, and had never presented with any symptoms before surgery. Case presentation A 56-year-old man underwent a total gastrectomy for stomach cancer. On postoperative Day 13, he suddenly developed presyncope, and blood tests showed hyperammonemia and high levels of serum citrulline. He was diagnosed with hepatic encephalopathy. DNA analysis revealed a heterozygote mutation in Solute Carrier Family 25. Although the patient received a conservative treatment, episodes of loss of consciousness and abnormality of behavior repeatedly occurred. Conclusion Abdominal surgery involving the reconstruction of digestive tract alters the mechanisms of absorption and/or metabolism such that the symptoms of adult-onset type II citurullinemia may arise. Liver transplantation should be performed if all conservative treatments are unsuccessful.